The Role of Game-Based Learning in Enhancing Economic Learning: A Systematic Literature Review - Imam Prawiranegara Gani (Penelitian dan Pengembangan Ilmu, 2024)
Game-based learning has gained significant attention in modern education, especially in the context of economics education, due to its ability to increase students' engagement and understanding of complex economic concepts. This systematic literature review aims to evaluate the effectiveness of the method using the PRISMA approach, involving the selection and analysis of relevant academic articles. The results show that game-based learning has a significant positive impact on students' understanding, increases engagement and practical application of economic theory and develops critical and analytical thinking skills. However, challenges such as suboptimal game design and the need for curriculum integration still exist. In conclusion, although game-based learning offers great potential to revolutionize economics education, further research is needed to address the challenges and optimize educational game design and implementation strategies in economics education environments.